KEHIDUPAN DUNIA PERSPEKTIF AL-QUR’AN (Kajian Terhadap Kata Al-Hayah Dan Kata Al-Ma’isyah) - Muhammad Alif Aziz; Muhammad Noupal; RA Erika Septiana (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2022)
Research entitled the life of the life of the world from the perspective of the Qur’an (study of the word al-Hayah end the word al-Ma’isyah) in this study, the interpretation of the science of interpretation with the word study method (tahlili) is used end this research uses library research, from here the research converys the background, namely the world life of the world al-Hayah end world al-Ma’isyah which contains a different meaning of life in a word of life in life in the Qur’an with the lauguage of the word life. Therefore, this study concludes in the view of the Qur’an that the word al-Hayah has the meaning of life end the word al-Ma’isyah has the meaning of life end livelihood, the meaning of the life of the world is taken from the surah Az-Zukhruf 43:32. The word al-Hayah has many meanings of life in the Qur’an as life in the meaning of line in the from of the life of the world of life which has the life of the world end has the life of the hereafter end the word al-Ma’isyah has two meanings of the word life end livelihood in life in the Qur’an, as life describes the life of the human image in the world end the hereafter in life end livelihood, which explains the picture of life in this world end in the hereafter.